2019
DOI: 10.1038/s41436-018-0131-4
|View full text |Cite
|
Sign up to set email alerts
|

Noncardiac genetic predisposition in sudden infant death syndrome

Abstract: A monogenic basis for SIDS amongst the previously implicated noncardiac genes and their encoded biological pathways is negligible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
(46 reference statements)
0
16
0
Order By: Relevance
“…Importantly, this does not suggest a lack of genetic contribution to SIDS; rather, it supports an extreme heterogeneity in the genetic causes which cannot be singled out by these methods in a cohort of this size (427 infants). Moreover, an investigation of all previously implicated noncardiac genes underpinning SIDS also failed to show any significant associations of ultrarare or novel variations consistent with autosomal dominant and recessive inheritance patterns . Therefore, it still needs to be investigated whether infant vulnerability to sudden death may be supported by a more complex polygenic inheritance model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this does not suggest a lack of genetic contribution to SIDS; rather, it supports an extreme heterogeneity in the genetic causes which cannot be singled out by these methods in a cohort of this size (427 infants). Moreover, an investigation of all previously implicated noncardiac genes underpinning SIDS also failed to show any significant associations of ultrarare or novel variations consistent with autosomal dominant and recessive inheritance patterns . Therefore, it still needs to be investigated whether infant vulnerability to sudden death may be supported by a more complex polygenic inheritance model.…”
Section: Discussionmentioning
confidence: 99%
“…significantly improved our understanding of the genetic basis of SIDS, 41,[43][44][45] but the magnitude of its contribution and the mode of inheritance are still obscure. A sequencing study of 161 infants who died of SIDS identified potentially causative gene variants in 20% of the children, and these were associated with inherited cardiac disorders and metabolic diseases.…”
Section: (2-4)mentioning
confidence: 99%
“…These infants and caregivers compose a population with potentially heightened anxiety among caregivers, limited evaluations, and short observation periods. Similar to sudden infant death syndrome, BRUE is unpredictable and without identified significant risk factors, 8,9 which may contribute to parental anxiety. Qualitative research allows us to study the knowledge and beliefs people have regarding a specific topic as it relates to their own experience and can help provide a detailed illustration of underlying constructs that affect caregivers during the hospitalization of their children.…”
mentioning
confidence: 99%
“…The authors indicate that this may be due to an extreme heterogeneity of aetiologies underlying SIDS. A study by Grey and Behr 22 performed an exome sequencing of non‐cardiac genes, but also this study failed to identify any specific biological pathway associated with SIDS.…”
Section: Discussionmentioning
confidence: 90%